A bovine papillomavirus constitutive enhancer is negatively regulated by the E2 repressor through competitive binding for a cellular factor. - Vande Pol, S B (1990)
The bovine papillomavirus type 1 long control region (LCR) contains DNA sequence elements involved in the regulation of viral transcription and replication. Differences in the levels of transcription have previously been noted between bovine papillomavirus type 1-infected rodent cell lines and bovine cells. To investigate these differences, fragments of the LCR were cloned into an enhancer-deleted chloramphenicol acetyltransferase expression vector and assayed for enhancer activity. A strong constitutive enhancer was found in the 5' portion of the LCR that was most active in primary bovine fibroblasts and had little activity in other cell types. Deletion mapping localized most of the activity to a 113-bp fragment from nucleotides (nt) 7162 to 7275, a region of the viral sequence that also contains the P7185 promoter and an E2-binding site at nt 7203. The enhancer activity of this element could be positively modulated by the full-length E2 transactivator or negatively modulated by the E2 repressor. Site-directed mutagenesis defined two cis elements, CE1 and CE2, which were both necessary for enhancer activity. The CE1 element was required for P7185 activity, whereas the CE2 element was dispensable for P7185 activity. The CE1 and CE2 elements both overlap the E2-binding site at nt 7203. In vitro DNA-binding studies revealed (i) a specific gel retardation complex associated with cellular factor binding at the CE1 element, (ii) a correlation between enhancer activity and the binding of factors to the CE1 element, and (iii) competitive binding between the E2 repressor and the cellular factor at the CE1 element.